On the distinction of empathic and vicarious emotions - Paulus, Frieder M.; Müller-Pinzler, Laura; Westermann, Stefan; Krach, Sören (Frontiers in Human Neuroscience, 2013)
In the introduction to the special issue “The Neural Underpinnings of Vicarious Experience” the editors state that one “may feel embarrassed when witnessing another making a social faux pas”. In our commentary we address this statement and ask whether this example introduces a vicarious or an empathic form of embarrassment. We elaborate commonalities and differences between these two forms of emotional experiences and discuss their underlying mechanisms. We suggest that both, vicarious and empathic emotions, originate from the simulation processes mirroring and mentalizing that depend on anchoring and adjustment. We claim the term ‘empathic emotion’ to be reserved exclusively for incidents where perceivers and social targets have shared affective experience, whereas ‘vicarious emotion’ offers a wider scope and also includes non-shared affective experiences. Both are supposed to be highly functional in social interactions.